2023
DOI: 10.1037/emo0001158
|View full text |Cite
|
Sign up to set email alerts
|

Attention-focused emotion regulation in everyday life in adulthood and old age.

Abstract: Although some lab studies suggest older adults rely more on attentional deployment to regulate their emotions, little is known about age differences in specific attention deployment tactic use and how they relate to mood regulation in everyday life. The current longitudinal experience sampling study considered several different attention deployment tactics, such as shifting or focusing attention to positive and negative elements either internally or externally (thoughts and feelings vs. external environment). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 100 publications
0
4
0
Order By: Relevance
“…This study does not explore attentional deployment toward internal feelings, such as attention toward positive or negative emotions while watching the videos. Recent experience sampling work examined internal attention deployment tactics in everyday life and found that younger adults focused on thoughts and feelings less frequently than middle-aged and older adults (DiGirolamo et al, 2022). Future eye-tracking research could simultaneously evaluate the use of these tactics and fixation on positive and negative content in the home.…”
Section: Limitations/future Directionsmentioning
confidence: 99%
“…This study does not explore attentional deployment toward internal feelings, such as attention toward positive or negative emotions while watching the videos. Recent experience sampling work examined internal attention deployment tactics in everyday life and found that younger adults focused on thoughts and feelings less frequently than middle-aged and older adults (DiGirolamo et al, 2022). Future eye-tracking research could simultaneously evaluate the use of these tactics and fixation on positive and negative content in the home.…”
Section: Limitations/future Directionsmentioning
confidence: 99%
“…Sometimes, it may be difficult to distinguish between selection and modification strategies since the changes made in one situation may be perceived as creating a new situation instead [5,11,13]. • Attentional deployment: Strategies within this family are aimed to redirect attention between elements of the external environment or between personal thoughts [23,24]. Distraction and concentration are the most common strategies.…”
mentioning
confidence: 99%
“…Without clear evidence or a consistent pattern for age differences in strategy use in prior work, it is impossible to understand or test theories of age-related change in emotion regulation. However, recent work has identified some age differences in specific tactic types across strategies (DiGirolamo et al, 2023 ; Livingstone & Isaacowitz, 2021 ), suggesting that examining emotion regulation at the tactic level is the most meaningful for assessing age differences. Specifically, positivity-upregulating tactics across strategy types are most frequently used regardless of age, but older adults may use them even more (Livingstone & Isaacowitz, 2021 ).…”
mentioning
confidence: 99%
“…Although past studies testing only tactic frequencies (DiGirolamo et al, 2023 ; Livingstone & Isaacowitz, 2021 ) are suggestive that tactics are important for understanding age differences, testing frequencies alone cannot provide a precise snapshot of an individual’s emotion regulation behavior because it does not account for the hierarchical structure. It is impossible to test whether older adults rely on a different or more effective configuration without assessing individual differences in the relative reliance on some tactics versus others.…”
mentioning
confidence: 99%